Hecw controls oogenesis and neuronal homeostasis by promoting the liquid state of ribonucleoprotein particles - Valentina Fajner (Nature Portfolio, 2021)
Ribonucleoprotein (RNP) granules are responsible for mRNA transport and local translation required for neuronal and oocyte maturation. Here the authors show that loss of the Drosophila Ub ligase Hecw enlarges RNP granules, leads to a liquid to gel-like transition, and results in defective oogenesis and neuronal loss.